2002
DOI: 10.1121/1.1471898
|View full text |Cite
|
Sign up to set email alerts
|

Listener weighting of cues for lateral angle: The duplex theory of sound localization revisited

Abstract: The virtual auditory space technique was used to quantify the relative strengths of interaural time difference ͑ITD͒, interaural level difference ͑ILD͒, and spectral cues in determining the perceived lateral angle of wideband, low-pass, and high-pass noise bursts. Listeners reported the apparent locations of virtual targets that were presented over headphones and filtered with listeners' own directional transfer functions. The stimuli were manipulated by delaying or attenuating the signal to one ear ͑by up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
302
3
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(326 citation statements)
references
References 56 publications
18
302
3
3
Order By: Relevance
“…However, ILDs can occur, at least for the human listeners: Several studies have shown that also at frequencies below 1 kHz, ILDs of up to 5 dB are generated at sound-source distances around 1 m (Brungart and Rabinowitz 1999;Kuwada et al 2010). Even though both cues were shown to be present in low-frequency sounds, a recent study of Macpherson and Middlebrooks (2002) showed that listeners judged ITDs as the prominent cue to determine the azimuthal position of a low-frequency signal. Therefore, we did not implement ILDs in our simulation.…”
Section: Fig 5 Localization Thresholds and Resultant Release From Mmentioning
confidence: 99%
“…However, ILDs can occur, at least for the human listeners: Several studies have shown that also at frequencies below 1 kHz, ILDs of up to 5 dB are generated at sound-source distances around 1 m (Brungart and Rabinowitz 1999;Kuwada et al 2010). Even though both cues were shown to be present in low-frequency sounds, a recent study of Macpherson and Middlebrooks (2002) showed that listeners judged ITDs as the prominent cue to determine the azimuthal position of a low-frequency signal. Therefore, we did not implement ILDs in our simulation.…”
Section: Fig 5 Localization Thresholds and Resultant Release From Mmentioning
confidence: 99%
“…1.1(A)). Low frequency sounds are best lateralized by interpreting ITDs because of the loss of phase-locking in the auditory nerve with higher frequency sounds (Macpherson and Middlebrooks 2002). Normal-hearing listeners can recognize timing delays between ears of as small as 10 µs (Akeroyd 2006).…”
Section: Psychoacoustics Of Binaural Hearingmentioning
confidence: 99%
“…ILDs are greatest at high frequencies because at frequencies of less than 500Hz, wavelengths become larger than the diameter of a human listener's head, canceling out the effects of the head shadow (Macpherson and Middlebrooks 2002;Schnupp and Carr 2009). Normal-hearing adults can be sensitive to ILDs of as low as 0.5 dB (Akeroyd 2006;Harrison 1988).…”
Section: Psychoacoustics Of Binaural Hearingmentioning
confidence: 99%
“…Current benefits in sound localization are based primarily on interaural level difference (ILD) cues (van Hoesel 2004;Seeber and Fastl 2008;Aronoff et al 2010) and improvements in speech understanding in noise largely result from attending to the ear with the best signal-to-noise ratio (van Hoesel and Tyler 2003;Schleich et al 2004;Litovsky et al 2006). Importantly, bilateral CI users receive minimal benefit from interaural time difference (ITD) cues (van Hoesel 2012), which provide the greatest benefit to normal-hearing listeners in everyday situations (Bronkhorst and Plomp 1992;Zurek 1992;Macpherson and Middlebrooks 2002).…”
Section: Introductionmentioning
confidence: 99%